The Great Recession and adverse birth outcomes: Evidence from California, USA - Brian Karl Finch; Kyla Thomas; Audrey N. Beck (Elsevier, 2019)
Objectives: Prior studies of the health effects of recessions have shown mixed results. Ecological studies often report a positive relationship between economic downturns and population health while individual-level studies often show that conditions related to recessions are deleterious. Our study examines the spatially and temporally heterogenous effects of the Great Recession (TGR) on adverse birth outcomes, a contemporaneous measure of population health that is highly responsive to changing social conditions. Methods: We use restricted birth cohort data from California (2004-2012) merged with both county- and tract-level socio-demographic data, to explore birth selectivity and temporal and unemployment effects during TGR on adverse birth outcomes. Results: We find that gestational exposure - more specifically, second trimester exposure - during or adjacent to the months of TGR was generally deleterious for birth outcomes, more so, in some cases, for mothers with lower levels of education, and that increases in county-level unemployment were generally deleterious for birth outcomes. Conclusions: Although recessionary effects on population health are problematic and may have far-reaching effects, it appears that these effects may be largely universal, even given potential selective fertility favoring advantaged groups. Keywords: The great recession, Adverse birth outcomes